THE IMPORTANCE OF THE MINISTRY OF RELIGIOUS AFFAIRS’ LOVE-BASED CURRICULUM IN COUNTERING RADICALISM IN INDONESIA’S DIGITAL AGE - Ratna Sundari Puspitosari; Muhamad Slamet Yahya (Jurnal Konseling Pendidikan Islam, 2026)
This paper aims to analyze the urgency of the Ministry of Religious Affairs’ Love-Based Curriculum (KBC) as a comprehensive strategy to counter digital radicalism in Indonesia. This is a literature review in which data was collected from various sources, including books and articles on relevant topics. The research findings indicate that with a significant digital population, particularly among adolescents, there is a high vulnerability to extremist propaganda disseminated through social media. Unique characteristics of digital radicalism, such as rapid spread, targeting of specific demographics, and the formation of echo chambers, accelerate the dissemination of extremist ideologies among students. Based on the analysis, KBC has the potential to minimize this vulnerability by building psychosocial and cognitive resilience. KBC integrates universal values such as empathy, tolerance, and compassion to counter narratives of hatred and polarization. This curriculum emphasizes holistic character education, digital literacy, and ethics, empowering students to think critically and filter information responsibly. The position of the Love-Based Curriculum is highly relevant as a counter-narrative because it actively promotes positive values that are essential in combating radical ideologies. Thus, the Love-Based Curriculum is a strategic step toward realizing a more peaceful and just world.